Exploring Dental Providers’ Workflow in an Electronic Dental Record Environment - Schwei, Kelsey M; Cooper, Ryan; Mahnke, Andrea N.; Ye, Zhan; Acharya, Amit (Applied Clinical Informatics, 2016)
A workflow is defined as a predefined set of work steps and partial ordering of these steps in any environment to achieve the expected outcome. Few studies have investigated the workflow of providers in a dental office. It is important to understand the interaction of dental providers with the existing technologies at point of care to assess breakdown in the workflow which could contribute to better technology designs.The study objective was to assess electronic dental record (EDR) workflows using time and motion methodology in order to identify breakdowns and opportunities for process improvement.A time and motion methodology was used to study the human-computer interaction and workflow of dental providers with an EDR in four dental centers at a large healthcare organization. A data collection tool was developed to capture the workflow of dental providers and staff while they interacted with an EDR during initial, planned, and emergency patient visits, and at the front desk. Qualitative and quantitative analysis was conducted on the observational data.Breakdowns in workflow were identified while posting charges, viewing radiographs, e-prescribing, and interacting with patient scheduler. EDR interaction time was significantly different between dentists and dental assistants (6:20 min vs. 10:57 min, p = 0.013) and between dentists and dental hygienists (6:20 min vs. 9:36 min, p = 0.003).On average, a dentist spent far less time than dental assistants and dental hygienists in data recording within the EDR.
Keywords: Time and motion studies; dental clinics; workflow; dental records; health information systems; process assessment (health care)